Virus-like particles: Innovative strategies for combatting emerging and re-emerging viral threats - Bugude Laxmi; Palempalli Uma Maheswari Devi; Thanjavur Naveen; Viswanath Buddolla (The Microbe)
Virus-like particles (VLPs) are non-infectious nanostructures that closely mimic the architecture and surface features of native viruses while lacking genetic material. This structural resemblance, combined with their inherent safety, positions VLPs as powerful tools in addressing the growing challenges posed by emerging and re-emerging viral threats. This review highlights their significant contributions in three key areas: vaccine development, viral diagnostics, and environmental surveillance. In the field of vaccinology, VLPs have shown remarkable potential to elicit robust immune responses, making them suitable for designing multivalent and broad-spectrum vaccines, particularly against zoonotic and vector-borne viruses. In diagnostics, their use in assay development has significantly improved the sensitivity and specificity of viral detection, offering promise for rapid and accurate identification of pathogens. Moreover, VLPs are being increasingly explored in environmental monitoring systems, where they contribute to the early detection of viral pathogens in water and other ecological matrices. These applications not only enhance our understanding of virus transmission dynamics but also support public health preparedness. VLPs also serve as valuable tools for studying viral immune evasion mechanisms and host-pathogen interactions, contributing to our understanding of viral evolution. Their adaptability and multifunctionality suggest that VLPs will play an increasingly important role in global virology research, disease prevention, and pandemic preparedness.